2019
DOI: 10.1136/bmjopen-2019-029739
|View full text |Cite
|
Sign up to set email alerts
|

Do you recommend cancer screening to your patients? A cross-sectional study of Norwegian doctors

Abstract: ObjectiveGuidelines for cancer screening have been debated and are followed to varying degrees. We wanted to study whether and why doctors recommend disease-specific cancer screening to their patients.DesignOur cross-sectional survey used a postal questionnaire. The data were examined with descriptive methods and binary logistic regression.SettingWe surveyed doctors working in all health services.ParticipantsOur participants comprised a representative sample of Norwegian doctors in 2014/2015.Primary and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The current study findings showed that more than three-fourths of the physicians referred a patient for cancer screening at some point in their clinical practice. Our findings regard cancer screening are higher for CRC in the Al-Qassim region of Saudi Arabia at 64.5% vs 42% in Norway; this might be due to the fact that the project for CRC screening has been initiated by the Ministry of Health recently, while in Norway, the program was not initiated at the time of the survey [ 4 ]. However, the figure is lower than CRC screening recommendation rates in Riyadh (92%) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study findings showed that more than three-fourths of the physicians referred a patient for cancer screening at some point in their clinical practice. Our findings regard cancer screening are higher for CRC in the Al-Qassim region of Saudi Arabia at 64.5% vs 42% in Norway; this might be due to the fact that the project for CRC screening has been initiated by the Ministry of Health recently, while in Norway, the program was not initiated at the time of the survey [ 4 ]. However, the figure is lower than CRC screening recommendation rates in Riyadh (92%) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Survey items were based on a review of previous literature and were further validated by three consultants in preventive medicine and public health; they were tested through a pilot study among PHC physicians before the initiation of the study [ 4 , 21 - 23 ]. Reliability assessment for barriers for screening showed Cronbach's alpha to be 0.81 for system barriers, 0.72 for physicians' barriers, and 0.58 for patients' barriers; the overall Cronbach’s alpha was determined to be 0.838, which confirms that there is a high level of internal consistency and reliability for the questions used in eliciting participants’ responses on what they think to be the barriers to cancer screening recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The ambiguity about whether clinicians introduce discussion could lead to subjective screening decisions and impact the number of individuals counselled. 7 If the man is responsible, influences of their education level and health literacy may lead to health inequities. 8 Certain factors, such as African descent and family history, increase an individual's PCa risk.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting recent study from Norway, where Pap smears are routinely carried out by PHC physicians, Bringedal et al examined doctors’ characteristics to determine whether and why doctors recommended disease-specific cancer screening to their patients [ 22 ]. The study revealed that PHC physicians adhered to cancer screening guidelines more in general and that they recommended cervical cancer screening at a significantly higher rate in comparison to other specialists.…”
Section: Discussionmentioning
confidence: 99%